Streptococcus dentisani and dental caries in children. Literature review - López-Ramos, Roxana Patricia (2024)
Objective: To collect information on Streptococcus dentisani and dental caries in children. Mateial and Methods: A literature search was conducted in the Medline, EBSCO, Google Scholar and Scielo databases. The search terms used were: "Streptococcus dentisani", "Dental plaque", "Saliva", "Dental caries", "Children", as well as the corresponding terms in English. The search included articles in Spanish and English from the last 11 years that addressed the topic of Streptococcus dentisani and dental caries in children. Four studies were found, two studies mentioned that Streptococcus dentisani was seen more in children without dental caries than those with dental caries, this result was statistically significant, and two studies found the same, but found no significant differences. Conclusion: The data suggest that Streptococcus dentisani is a component of the oral microbiota negatively associated with dental caries. However, the scientific evidence is still limited in this population and further studies are required.